Cytotoxicity of various types of gold-mesoporous silica nanoparticles in human breast cancer cells - Liu G (Dove Medical Press, 2015)
Guomu Liu,1,* Qiongshu Li,1,2,* Weihua Ni,1 Nannan Zhang,1 Xiao Zheng,3 Yingshuai Wang,4 Dan Shao,3 Guixiang Tai1 1Department of Immunology, College of Basic Medical Sciences, Jilin University, Changchun, 2Shenzhen Beike Cell Engineering Research Institute, Yuanxing Science and Technology Building, Nanshan, Shenzhen, 3Department of Pharmacology, Nanomedicine Engineering Laboratory of Jilin Province, College of Basic Medical Sciences, 4State Key Laboratory on Integrated Optoelectronics, College of Electronic Science and Engineering, Jilin University, Changchun, People’s Republic of China*These authors contributed equally to this workAbstract: Recently, gold nanoparticles (AuNPs) have shown promising biological applications due to their unique electronic and optical properties. However, the potential toxicity of AuNPs remains a major hurdle that impedes their use in clinical settings. Mesoporous silica is very suitable for the use as a coating material for AuNPs and might not only reduce the cytotoxicity of cetyltrimethylammonium bromide-coated AuNPs but might also facilitate the loading and delivery of drugs. Herein, three types of rod-like gold-mesoporous silica nanoparticles (termed bare AuNPs, core–shell Au@mSiO2NPs, and Janus Au@mSiO2NPs) were specially designed, and the effects of these AuNPs on cellular uptake, toxic behavior, and mechanism were then systematically studied. Our results indicate that bare AuNPs exerted higher toxicity than the Au@mSiO2NPs and that Janus Au@mSiO2NPs exhibited the lowest toxicity in human breast cancer MCF-7 cells, consistent with the endocytosis capacity of the nanoparticles, which followed the order, bare AuNPs > core–shell Au@mSiO2NPs > Janus Au@mSiO2NPs. More importantly, the AuNPs-induced apoptosis of MCF-7 cells exhibited features that were characteristic of intracellular reactive oxygen species (ROS) generation, activation of c-Jun-N-terminal kinase (JNK) phosphorylation, an enhanced Bax-to-Bcl-2 ratio, and loss of the mitochondrial membrane potential. Simultaneously, cytochrome c was released from mitochondria, and the caspase-3/9 cascade was activated. Moreover, both ROS scavenger (N-acetylcysteine) and JNK inhibitor (SP600125) partly blocked the induction of apoptosis in all AuNPs-treated cells. Taken together, these findings suggest that all AuNPs induce apoptosis through the ROS-/JNK-mediated mitochondrial pathway. Thus, Janus Au@mSiO2NPs exhibit the potential for applications in biomedicine, thus aiding the clinical translation of AuNPs. Keywords: gold nanoparticles, cytotoxicity, gold-mesoporous silica Janus nanoparticles, reactive oxygen species, c-Jun-N-terminal kinase, mitochondrial apoptosis